2019
DOI: 10.1002/ddr.21582
|View full text |Cite
|
Sign up to set email alerts
|

Quinalizarin induces cycle arrest and apoptosis via reactive oxygen species‐mediated signaling pathways in human melanoma A375 cells

Abstract: Quinalizarin, a bioactive and highly selective compound, is known to promote apoptosis in colon and lung cancer cells. However, studies evaluating quinalizarin‐induced apoptosis in melanoma cells have not been conducted. In the present study, we investigated the underlying mechanisms of antimelanoma activity of quinalizarin in human melanoma A375 cells. The MTT assay and Trypan blue staining were used to evaluate the cell viability. The flow cytometry was used to detect cell cycle, apoptosis and reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Many studies have reported that anthraquinone components affect the cell differentiation, migration, and apoptosis of various genetic and pathological types of human cancer cell lines 26,27 . Similarly, as one type of anthraquinone, Quina inhibits the proliferation and accelerates apoptosis of different human tumor cells 28,29 . In the current study, we demonstrated the effects of Quina on human esophageal cancer cell proliferation, apoptosis, and cell cycle distribution.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Many studies have reported that anthraquinone components affect the cell differentiation, migration, and apoptosis of various genetic and pathological types of human cancer cell lines 26,27 . Similarly, as one type of anthraquinone, Quina inhibits the proliferation and accelerates apoptosis of different human tumor cells 28,29 . In the current study, we demonstrated the effects of Quina on human esophageal cancer cell proliferation, apoptosis, and cell cycle distribution.…”
Section: Discussionsupporting
confidence: 56%
“…26,27 Similarly, as one type of anthraquinone, Quina inhibits the proliferation and accelerates apoptosis of different human tumor cells. 28,29 In the current study, we demonstrated the effects of Quina on human esophageal cancer cell proliferation, apoptosis, and cell cycle distribution. In particular, we studied the effects of Quina on the survival and growth of the human esophageal cancer HCE-4 cells in vitro and showed that it obviously inhibited the proliferation of HCE-4 cells.…”
Section: Discussionmentioning
confidence: 60%
“…Some natural compounds can directly target STAT3. Quinalizarin, also known as 1,2,5,8-tetrahydroquinone, is a dual anthraquinone compound derived from the roots of the Rubiaceae herb ( 201 ). Quinalizarin is a compound found in several herbal remedies that have anti-tumor properties.…”
Section: Regulation Of Stat3 In Ecmentioning
confidence: 99%
“…Melanoma, also known as malignant melanoma, is a malignant tumor caused by abnormally rapid proliferation of melanocytes [ 15 ]. It is more common in skin, pia meninga, choroid and other parts of the eye [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damage or over activation of certain components of these pathways may lead to malignant transformation and the development of cancer. In the present study, we consider that signaling pathways such as cyclin/CDK, Ras/Raf/MEK/MAPK [ 19 ], JNK/C-Jun/AP-1, PI3K/Akt/PTEN/mTOR [ 20 ], IKK/I-κB/NF-κB [ 21 ], Wnt/β-catenin [ 22 ], Notch, Jak/STAT [ 15 ], MITF and some growth factors regulate the cycle progression, apoptosis and development of melanoma cells. However, no ideal inhibitor has appeared thus far, and there are still no inhibitors approved for marketing.…”
Section: Introductionmentioning
confidence: 99%